Draft genome of the famous ornamental plant Paeonia suffruticosa - Lv, Shuzuo; Cheng, Shu; Wang, Zhanying; Li, Shiming; Jin, Xin; Lan, Lei; Yang, Bing; Yu, Kang; Ni, Xuemei; Li, Ning; Hou, Xiaogai; Huang, Gang; et al. (Ecology and evolution, 2020)
Tree peony (Paeonia Sect. Moutan) is a famous ornamental plant, with huge historical, cultural, and economic significance worldwide. In this study, we reported the ~13.79 Gb draft genome of a wide‐grown Paeonia suffruticosa cultivar “Luo shen xiao chun,” representing the largest sequenced genome in dicots to date. Phylogenetic analyses based on genome sequences demonstrated that P. suffruticosa was placed as sister to Vitales, and they together formed a clade that was sister to Rosids, weakly supporting a relationship of ((Saxifragales and Vitales) and Rosids). The identification and expression analysis of MADS‐box genes based on the genome assembly and de novo transcriptome assembly of P. suffruticosa revealed that the function of C class genes was restricted in flower development, which might be responsible for the stamen petalody in tree peony cultivars. Overall, the first sequenced genome in the family Paeoniaceae provides an important resource for the origin, domestication, and evolutionary study as well as cultivar breeding in tree peony. Tree peony (Paeonia Sect. Moutan) is a famous ornamental plant, with huge historical, cultural, and economic significance worldwide. The presented genome assembly in this study would serve as an important resource for functional genomic and genetic studies on tree peony, which would be useful for the conservation of endangered wild paeonia species and exploring the mechanisms of plant diversification and adaption under domestication in various environments.